THE HIDDEN COSTS OF LABOR PRESENTEEISMIN LIMA MANUFACTURING COMPANIES: 2012 - Valera Loza, Daniel Hernán (2015)
The present study though the use of a descriptive correlational design, determined the costing of labor presenteeism in manufacturing companies in Lima, in 2012. A structured questionnaire was applied on 53 manufacturers of Lima, surveying a total of 903 workers, being 36.7 % men and 63.3 % women. The questionnaire was previously validated in a national sampling, in more than 211 companies, and held the scales of presenteeism, absenteeism and tardiness of staff, all with high levels of internal consistency and constructed validity using factor analysis. We found the result that labor costs accounted for Lima presenteeism has a significant loss of 3,725,463,000 soles per year, equivalent to 1,432,870,000 US dollars per year, or 0.78% of Gross Domestic Product. In addition, the costs of presenteeism, for the manufacturing sector represented a high percentage of total costs (75.2 %) compared to the costs of absenteeism (23.74 %) and tardiness (1.04%). It is recommended to create models of performance management that includes within its components the control and management of presen-teeism, emphasizing prevention.